A novel acceleration criterion for remote-end grounding-fault in MMC-MTDC under communication anomalies. (October 2022) - Tong, Ning; Tang, Zhenjie; Lai, Chun Sing; Li, Xue; Vaccaro, Alfredo; Lai, Loi Lei
Highlights: A novel acceleration criterion is proposed to trip the remote-end fault when the local-end protection fails due to the lack of sensitivity. Remote-end dead-zone faults can be identified without using communication and synchronization. With high sensitivity, in most cases, a 300 Ω resistive coverage can be achieved for remote-end dead-zone faults. With high speed, remote-end grounding faults can be isolated before the blocking of the local MMC converter. Abstract: The multi-terminal HVDC system based on the modular multilevel converter (MMC-MTDC) has very high technical merits for long-distance, flexible power transmission. In recent years, there has been a significant improvement in developing its fast-speed primary protection, especially for local-measurement-based ones immune to communication anomalies. However, in many cases, the problem of remote-end fault identification for the local-measurement-based protection elements needs further studies, mainly because such protection elements should balance between sensitivity and security. This paper proposes a novel acceleration criterion to identify remote-end faults for the MMC-MTDC. Based on the difference of the traveling wave propagation characteristics between the scenario of internal faults and that of the external fault, the local-end protection element will detect a highly-oscillating signal due to the opening of the remote-end DC circuit breaker. In contrast, no such signal will be observed in the external fault scenario. The wavelet time entropy is utilized to quantify the feature of oscillation. The performance of the proposed criterion is assessed based on the established four-terminal MMC-MTDC on the PSCAD/EMTDC platform. Results indicate that by using the proposed criterion, the sensitivity of the local-measurement-based protection element against remote-end faults is greatly enhanced.